2018
DOI: 10.1007/s12192-018-0895-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical heat shock protein 70 prevents imiquimod-induced psoriasis-like inflammation in mice

Abstract: Psoriasis is a chronic inflammatory skin disease with systemic manifestations and potential genetic etiology. The newest treatments utilize antibodies against one of several cytokines known to underlie the inflammatory signaling molecules that produce the skin and systemic symptoms. However, these agents must be regularly injected, and they may compromise the normal responses of the immune system. Furthermore, they do not address the causes of the abnormal immunoregulatory responses of the disease because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…This demonstration extends previous reports of a therapeutic potential of targeting Hsp70 by topical approaches in the IMQ mouse model as well as by Hsp70 vaccination in animal models of different autoimmune diseases such as rheumatoid arthritis and lupus erythematosus ( 4 6 , 9 , 10 ). In fact, there is also some evidence from a randomized controlled trial in which intravenous administration of the endoplasmic reticulum Hsp70 family member binding immunoglobulin protein (BiP) to patients with rheumatoid arthritis was associated with clinical and biological improvements in the disease activity ( 23 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This demonstration extends previous reports of a therapeutic potential of targeting Hsp70 by topical approaches in the IMQ mouse model as well as by Hsp70 vaccination in animal models of different autoimmune diseases such as rheumatoid arthritis and lupus erythematosus ( 4 6 , 9 , 10 ). In fact, there is also some evidence from a randomized controlled trial in which intravenous administration of the endoplasmic reticulum Hsp70 family member binding immunoglobulin protein (BiP) to patients with rheumatoid arthritis was associated with clinical and biological improvements in the disease activity ( 23 ).…”
Section: Discussionsupporting
confidence: 87%
“…Recently, an equivocal role of Hsp70 has been demonstrated in the imiquimod (IMQ)-induced skin inflammation mouse model which has become the most widely used murine model for preclinical studies of psoriasis-like dermatitis ( 9 11 ). While one study showed that topical application of Hsp70 led to a reduction of skin lesions and inflammatory markers ( 10 ), another study described similar effects using a topical Hsp70 inhibitor ( 9 ). Here, we further defined the role of Hsp70 (using murine [m]-, human [h]-, or plant [p]-Hsp70) as a treatment target in the IMQ mouse model and related in vitro assays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine in turn can activate expression of CXCL9/10 genes coding for chemokines attracting CD8(+) T cells (Jacquemin et al 2017). Importantly, it has been recently found that topical application of a cream containing high concentration of inducible HSPA derived from alfalfa plant ( Medicago sativa ) onto murine skin reduced skin inflammation in experimental psoriatic-like lesions induced by imiquimol (Seifarth et al 2018).…”
Section: Essentials About the Hspa1 A Member Of The Conservative Hspmentioning
confidence: 99%
“…Although recent biologic agents targeting different pro-inflammatory cytokines have revolutionized the management of psoriasis, these agents do not address the causes of the abnormal immunoregulatory responses of the disease, because the aetiology is not yet completely understood. The 70-kDa heat shock proteins (HSP70) are known to be potent immunomodulators, and their anti-inflammatory activity has recently been investigated in a murine psoriasis-like model (9).…”
mentioning
confidence: 99%